Phytochemical constituents and ethnopharmacological properties of Ageratum conyzoides L. (10th July 2019) - Yadav, Neelam; Ganie, Showkat Ahmad; Singh, Bijender; Chhillar, Anil K.; Yadav, Surender Singh
Abstract : Ageratum conyzoides L. (Asteraceae) is an invasive aromatic herb with immense therapeutic importance. The herb is distributed in tropical and subtropical regions. A .  conyzoides has imparted numerous ethnomedicinal uses because it has been used to cure various ailments that include leprosy, skin disorders, sleeping sickness, rheumatism, headaches, dyspnea, toothache, pneumonia and many more. A number of phytoconstituents have been scrutinized such as alkaloids, flavonoids, terpenes, chromenes, and sterols from almost every part of this plant. These phytoconstituents have shown diverse pharmacological properties including antimicrobial, anti‐inflammatory, analgesic, antioxidant, anticancer, antiprotozoal, antidiabetic, spasmolytic, allelopathy, and many more. The plant A .  conyzoides has provided a platform for doing pharmaceutical and toxicological research in order to isolate some promising active compounds and authenticate their safety in clinical uses. A .  conyzoides provides principal information for advanced studies in the field of pharmaceutical industries and agriculture. Present review article describes the cytogenetics, ethnobotany, phytochemistry, pharmacology, and toxicological aspects of A .  conyzoides .